MODALITAS DALAM TEKS BERITA HOAKS: KAJIAN LINGUISTIK SISTEMIK FUNGSIONAL - Amrullah, Firda; Yassi, Abdul Hakim; Gusnawaty, Gusnawaty (Universitas Hasanuddin, 2020)
This study aimed to examine the use of modality in news text. This research expected to improve public media literacy in identifying hoax news through modality analysis. This research presented qualitative descriptive data with systemic functional linguistic approach. This study focused on type, value, and modality orientation. The research data resource was Hoax Report of Legislative and President Election Internet Content Control Sub-directorate for the period of August 2018 by Ministry of Communication and Information of Republic Indonesia. The research result showed that modality type possibility modalization intermediate degree and modulity type obligation modulation intermediate degree to dominate other types of modality. There were also types of modality that were not found in hoax-text news. They were modality type of usuality modalization of medium degree and modality type of inclination modulation of low degree.